Empowering People with Cognitive Disabilities to Live Independently By Supporting Their Self-Management of Food and Related Expenses - (:unkn) unknown (My University, 2020)
People with ADHD (attention deficit hyperactivity disorder) often have difficulty in planning and organization that can impact their eating habits and lifestyle. We have created a novel mobile software application to support choosing meals and making healthy food purchases that meet dietary preferences within a specified budget. The core functions allow 1) Managing user profiles to support personalization 2) Obtaining recipe recommendations to fit profile, budget, and foods-on-hand 3) Planning food purchases, and 4) Reviewing foods-on-hand, budget and the nutritional balance of recent meals and food purchases.The application supports self-introspection to help people with ADHD review their history of food purchases and consumption, using both scrollable inventories and visualizations of their aggregated behavior. These functions allow users to easily see how their choices distribute across different broad categories of food. This information provides a basis for them to make more informed decisions on their future purchases, while being mindful of the most and least frequently discarded foods. A user study was conducted to assess the usability of the app and to determine how different patterns of use correlate with food or shopping related behaviors that might impact the target population. 65% of the subjects found that providing the various types of data requested seemed relevant and easy to do. On the other hand, 84% of the subjects feel that charts helped them to understand how well they were doing at keeping a budget, using foods, and not throwing away much.